AHP-TOPSIS AND ANOVA METHOD APPROACH IN SOFTWARE DEVELOPMENT CRITERIA SELECTION ACCORDING TO ISO 12207:2017 - Fadilla, Rizqi Mirza; Ariatmanto, Dhani (Universitas Royal, 2025)
Abstract: The rapid development of information technology has increased the demand for high-quality software, necessitating a structured development process. ISO/IEC/IEEE 12207:2017 serves as an international standard encompassing organizational, technical, and project support processes, differing from ISO 9001, which focuses more generally on quality management. This study employs a Multi-Criteria Decision Making (MCDM) approach by integrating the Analytic Hierarchy Process (AHP) and the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). AHP determines the weight of ISO 12207:2017 criteria through pairwise comparisons, while TOPSIS ranks software development activities based on these weights. To validate the results, Analysis of Variance (ANOVA) is applied. The findings indicate that the Software Requirements Definition Process has the highest priority weight (0.169), followed by Implementation (0.101) and Operation (0.095). Software Configuration Management is identified as the most critical activity with the highest TOPSIS score (0.221). ANOVA confirms the reliability of expert evaluations, showing no significant differences. This study provides a structured decision-making framework based on ISO 12207:2017, helping optimize software project management while ensuring alignment with international standards and industry best practices. Keywords: AHP; TOPSIS; ANOVA; ISO 12207:2017 Abstrak: Perkembangan teknologi informasi meningkatkan permintaan perangkat lunak berkualitas tinggi, sehingga diperlukan proses terstruktur dalam pengembangannya. ISO/IEC/IEEE 12207:2017 menjadi standar internasional yang mencakup proses organisasi, teknis, dan pendukung proyek, berbeda dengan ISO 9001 yang lebih umum pada manajemen kualitas. Penelitian ini menggunakan Multi-Criteria Decision Making (MCDM) dengan mengintegrasikan Analytic Hierarchy Process (AHP) dan Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). AHP menentukan bobot kriteria ISO 12207:2017 melalui perbandingan berpasangan, sementara TOPSIS memeringkat aktivitas pengembangan berdasarkan bobot tersebut. Untuk validasi, Analysis of Variance (ANOVA) diterapkan. Hasil penelitian menunjukkan bahwa Proses Definisi Kebutuhan Perangkat Lunak memiliki bobot tertinggi (0,169), diikuti Implementasi (0,101), dan Operasi (0,095). Manajemen Konfigurasi Perangkat Lunak menjadi aktivitas paling kritis dengan skor TOPSIS tertinggi (0,221). ANOVA mengonfirmasi keandalan penilaian para ahli tanpa perbedaan signifikan. Penelitian ini memberikan kerangka kerja pengambilan keputusan berbasis ISO 12207:2017, membantu optimalisasi manajemen proyek perangkat lunak, serta memastikan keselarasan dengan standar internasional dan praktek terbaik industri. Kata kunci: AHP; TOPSIS; ANOVA; ISO 12207:2017